Rapid Conversion of Sorbitol to Isosorbide in Hydrophobic Ionic Liquids under Microwave Irradiation. Issue 12 (15th September 2014) - Kamimura, Akio; Murata, Kengo; Tanaka, Yoshiki; Okagawa, Tomoki; Matsumoto, Hiroshi; Kaiso, Kouji; Yoshimoto, Makoto
Abstract Sorbitol was effectively converted to isosorbide by treatment with [TMPA][NTf2] in the presence of catalytic amounts of TsOH under microwave heating at 180 °C. The reaction completed within 10 min and isosorbide was isolated to about 60 %. Ionic liquids were readily recovered by an extraction treatment and reused several times.